THE POSITIVE AND NEGATIVE IMPACT OF RUNNING ON MENTAL HEALTH: A CURRENT LITERATURE REVIEW - Jan Nowak; Bartłomiej Czarnecki; Illia Koval; Bartosz Zwoliński; Wiktor Kubik; Kacper Sukiennicki; Wirginia Bertman; Katarzyna Szewczyk; Kamil Borysewicz; Klaudia Romejko; Natalia Kołdej; Zuzanna Kępczyńska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Mental health is a critical component of overall well-being, shaping daily functioning and resilience. Amid rising stress and the increasing prevalence of mood and anxiety disorders, interventions that enhance psychological well-being are of growing interest, including physical activity. Running, as an accessible and cost-effective exercise, has been associated with mood improvement, stress reduction, and decreased risk of mental health disorders. Despite robust evidence of its benefits, individual differences and potential limitations in psychological responses to running remain underexplored. This review synthesizes recent research on the physiological and psychological mechanisms linking running to mental health, highlighting its impact on stress, depressive symptoms, and overall well-being. Understanding these multidimensional effects can inform tailored, evidence-based strategies for promoting mental health through running. Methods: This review synthesizes recent literature (2015–2025) on running and mental health. A comprehensive search of PubMed, Scopus, and Google Scholar was conducted using keywords including "running," "mental health," "depression," and "psychological well-being." All relevant studies were considered to provide an inclusive overview of current evidence. Aim of The Study: The aim of this perspective review is to synthesize and critically evaluate current research on the effects of running on mental health as documented in the recent literature. Conclusion: Running constitutes a multidimensional activity with both beneficial and potentially adverse effects on mental health. Evidence supports its role in reducing depression and anxiety symptoms, enhancing mood, cognitive function, and self-efficacy. Effective use of running as a mental health intervention requires consideration of individual differences in motivation, personality, and emotional state, alongside strategies to balance physical exertion with psychological well-being and prevent burnout. Future research should adopt an interdisciplinary approach, integrating psychology, physiology, and public health, to elucidate mechanisms underlying these effects. Such insights can inform personalized and sustainable training recommendations, promoting both physical performance and long-term psychological well-being.